Catalogue of Inbiomyiidae (Diptera, Carnoidea) - Pereira-Colavite, Alessandre; Mello, Ramon Luciano (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The first catalogue of the Inbiomyiidae (Diptera, Carnoidea) is presented. The family includes 11 described species in the single genus Inbiomyia Buck, known from Bolivia, Colombia, Costa Rica, Ecuador, French Guiana, Peru and Venezuela. Four unnamed species, from Guatemala, Honduras, Ecuador and Bolivia, are listed. Information about author, year of publication, page number, type genus, type species, type locality, geographical distribution and references are given to the categories of family, genus and species. Referential maps are included to all described species.